Online Child Sexual abuse in the Gambia the Luring Strategies: The Perspective of Child Protection Officers (Case Study: Serekunda Tourism Development Areas) - Yahya Muhammed Bah; Myrtati Dyah Artaria (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The rapid expansion of digital technology has increased global connectivity but simultaneously created new avenues for online child sexual abuse and exploitation, particularly in vulnerable tourism-driven settings such as The Gambia. Objective: This study aims to examine the luring strategies used by perpetrators, identify contributing factors, and explore existing prevention and support mechanisms from the perspective of child protection officers. Method: A qualitative case study approach was employed involving in-depth interviews with 29 child protection officers working with issues related to the Tourism Development Areas. Data were analysed thematically to capture patterns related to recruitment techniques, impacts, and institutional responses. Result: Findings reveal that perpetrators employ diverse strategies, including social media befriending, smartphone access, manipulation of families and communities, trafficking networks, peer influence, drug use, gifts, and intermediaries such as pimps. Limited parental supervision, poverty, and widespread digital access significantly increase children’s vulnerability. Conclusion: Online platforms have intensified both the scale and complexity of child sexual exploitation, requiring coordinated, multi-level interventions. Contribution: This study provides empirical insights to inform policy development, strengthen child protection systems, and support targeted prevention strategies in the tourism development areas and their environment.